Using Open Educational Resources at Viterbo University: Faculty and Student Feedback - Oelfke, Alissa L.; Sadowski, Jennifer A.; Mathwig Ramseier, Cari; Iremonger, Christopher; Volkert, Katrina; Dykman, Emily; Kuhl, Lynne; Baumann, Annie (International Review of Research in Open and Distributed Learning, 2021)
This study evaluated a coordinated and collaborative pilot implementation of open educational resources (OER) across multiple disciplines including nursing, accounting, environmental science, religious studies, and finance. Participating faculty were qualitatively surveyed regarding their experience creating and implementing OER in a course. Students were surveyed on their perceptions of OER quality, cost savings, and ease of use. Faculty had an overall positive experience with OER, believing there was a significant benefit to students in cost savings while maintaining learning quality. Faculty felt the OER implementation process took a significant investment of time and recommended that faculty should be compensated for creating and implementing OER materials in future courses. Students overall showed positive responses to using OER in their course; the majority of students agreed with the OER cost savings, quality of OER resources, ease of using OER, and they trusted the use of OER materials. Older students (over 30 years) were more likely to state they would print out OER materials rather than read them online (as compared with students 30 and under). Senior-level students agreed significantly more than did freshman-level students that OER presented a cost savings. Faculty recommendations from this study included focusing on courses with very high textbook costs and courses that would impact the greatest number of students. Additionally, faculty recommended a follow-up revision process to keep OER materials current after implementation.